Key Trends in Implementation of the Fund's Transparency Policy. (Policy Papers; Policy Paper ;, 2006)
At the time of the 2005 review of the Fund's transparency policy, it was agreed that information on key trends in implementation of the transparency policy would be circulated to the Board regularly, along with lists indicating the publication status of reports discussed by the Board (see IMF Executive Board Reviews Fund's Transparency Policy, August 15, 2005 and The Fund's Transparency Policy-Proposed Amendments, July 28, 2005). The set of Tables provided in this report focuses on documents published through December 2005.